Pressure-assisted isolation of micro- and nanoplastics from food of animal origin with special emphasis on seafood - Julia Süssmann; Elke Walz; Birgit Hetzer; Ralf Greiner; Elke Kerstin Fischer; Sascha Rohn; Jan Fritsche (Journal of Consumer Protection and Food Safety, 2025)
Recent studies have indicated the presence of micro- and nanoplastics in food of animal origin. To address the concerns regarding human dietary plastic uptake, extensive monitoring using validated analytical methods is required. However, a major challenge in analysis lies in the high complexity of preparing food samples rich in macromolecular content (e.g., proteins, complex lipids), such as seafood. Consequently, this study aimed to optimise sample preparation methods for seafood, meat, milk, honey, and eggs, ensuring negligible impact on plastic integrity. Sample matrices were digested using combinations of alkaline, oxidative, and enzymatic approaches, with incubation periods ranging from 6 to 16 h. Particles were rapidly isolated by pressure-assisted filtration, which retained particles in the lower micron range. This method, used for isolating microplastic from food, was compared to the commonly employed vacuum filtration technique. Pressure-assisted filtration improved filtration rates and matrix removal while demonstrating comparable impact on procedural contamination and polymer integrity to vacuum filtration. The feasibility of microplastic analysis was demonstrated using fluorescence imaging. In contrast to microplastics, nanoplastics (< 1 µm) have greater potential for negative biological effects due to their small size, warranting detailed analysis. However, their low particle mass, susceptibility for agglomeration, and the detection limits of conventional spectroscopic techniques pose unique analytical challenges. Addressing these challenges is essential for developing standardised methodologies, including certified food reference material, to enable safety assessments of micro- and nanoplastic in food. Graphical Abstract